A Comparison between the Kawase and Extended Retrosigmoid Approaches (Retrosigmoid Transtentorial and Retrosigmoid Intradural Suprameatal Approaches) for Accessing the Petroclival Tumors. A Cadaveric Study - Sharma, Mayur; Ambekar, Sudheer; Guthikonda, Bharat; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2014)
Background The aim of our study was to compare the area of exposure at the ventral brainstem and petroclival region offered by the Kawase, retrosigmoid transtentorial (RTT), and the retrosigmoid intradural suprameatal (RISA) approaches in cadaveric models.Methods We performed 15 approaches (five each of the Kawase, RISA, and RTT approaches) on silicone-injected adult cadaver heads. Ventral brainstem and petroclival areas of exposure were measured and compared.Results The mean ventral brainstem area exposed by the Kawase approach was 55.00 ± 24.1 mm2, significantly less than that exposed by RTT (441 ± 63.3 mm2) and RISA (311 ± 61 mm2) (p < 0.05). The area of ventral brainstem exposure was significantly more via RTT than through RISA (p = 0.01). The mean petroclival area of exposure through the Kawase approach was significantly smaller than that obtained through the RTT and RISA approaches (101.7 ± 545.01 mm2, 696 ± 57.7 mm2, and 716.7 ± 51.4 mm2, respectively).Conclusion Retrosigmoid approaches provide a greater exposure of the brainstem and petroclival areas. The Kawase approach is ideally suited for lesions around the Meckel cave with an extension into the middle fossa. These approaches can be used in conjunction with one another to access petroclival tumors.
Keywords: Kawase; retrosigmoid; transtentorial; suprameatal; petroclival tumors.